Sustainable Employability in the Mid and Late Career: An Integrative Review - Carlos-María Alcover; Greta Mazzetti; Michela Vignoli (Journal of Work and Organizational Psychology, 2021)

(untitled)
In the last decade, interest in investigating the sustainable employability (SE) of older workers has gained ground, generating a significant number of theoretical and empirical contributions. However, the construct of SE lacks a definition accepted by the scientific community and unified measurement criteria, which has led to results that, so far, do not allow us to draw solid conclusions on its relevance. The aim of this integrative review is twofold. Firstly, we review the theoretical formulations and definitions proposed, as well as the main empirical results of the studies and interventions on SE. Our review includes 31 studies (26 empirical and five theoretical; total sample size N = 33,368). Secondly, proposals and suggestions are offered aimed at integrating the previous results and advancing in the definition, operationalization, and measurement of SE, with the ultimate goal of increasing its value for future research in the mid-and late-career domain.